MENINGKATKAN KINERJA MELALUI PENGUATAN DISIPLIN DAN PERAN KEPEMIMPINAN - Hendri Prasetyo; Azalia Nuristiqomah (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The company realizes that the achievement of goals is due to employee performance. Therefore, the company feels the need to pay attention to various factors that strengthen the increase in performance, including strengthening work discipline and optimizing the role of leadership. In reviewing the research phenomenon, a quantitative approach is used with the causal associative method. Then data was collected by distributing questionnaires to a predetermined number of respondents. The data collected were analyzed using multiple linear regression statistical techniques. The research was conducted at PT Mega Central Finance Fatmawati, and the unit of research analysis was 50 employees. The results of the study confirm that there is a strong causal relationship between performance with discipline and leadership style. This means that performance will increase along with strengthening the role of leadership, both in interacting and in carrying out managerial functions (supervision). Likewise with work discipline, there is a tendency for performance to increase when disciplined awareness increases. Thus, companies need to maintain a culture of discipline in order to form regular work behavior, then need to maintain leadership behavior that supports performance improvement.